Changing Paradigms in Antibiotic Resistance in Salmonella Species with Focus on Fluoroquinolone Resistance: A 5-Year Retrospective Study of Enteric Fever in a Tertiary Care Hospital in Kolkata, India - Malabika Biswas; Silpak Biswas; Bishal Gupta; Maria Teresa Mascellino; Anindita Rakshit; Banya Chakraborty (MDPI AG, 2022)
Enteric fever, a potentially fatal multisystem disease that is caused by Salmonella enterica serovar Typhi and Paratyphi, poses a significant risk in low- and middle-income countries. A retrospective study to understand the prevalence and evolving patterns of antibiotic resistance in Salmonella Typhi and Paratyphi was undertaken from June 2017 to June 2022. A total of 4051 blood samples were collected from patients attending inpatient and outpatient departments of the School of Tropical Medicine (Kolkata, India) hospital. Blood samples were cultured, and culture positive samples were further processed for identification using conventional and automated systems. Antibiotic susceptibility test was performed using both the Kirby-Bauer disc diffusion method and VITEK2 (bioMerieux). Forty-five (1.1%) Salmonella species were isolated among the number of total (n = 4051) samples that were tested. Out of the 45 Salmonella isolates, 35 were Salmonella Typhi (77.77%) and 10 were Salmonella Paratyphi A (22.23%). We found pronounced fluoroquinolone resistance of 100% in the recent years (2019-2022) in both of the S. Typhi and S. Paratyphi A isolates. We found that 1 Salmonella Typhi and 2 Salmonella Paratyphi A isolates were resistant against multiple antibiotics (cefixime, ceftriaxone, ciprofloxacin and nalidixic acid), and 1 multidrug-resistant (MDR) Salmonella Paratyphi A isolate was found in a recent study year (2020) and it showed resistance against different classes of antibiotics (cephalosporins, fluoroquinolones and carbapenems). There was no resistance that was detected to the 3rd generation cephalosporins in the final years of the study. The emergence of Salmonella isolates that are resistant to multiple antibiotics poses a serious health problem. The antimicrobial resistance patterns that were detected in the study thus warrant further studies to understand the antibiotic susceptibility and resistance pattern of Salmonella against the major classes of antibiotics.